Indian journal of pharmaceutics (New Delhi International Science Press)
The Indian Journal of Pharmaceutics is a peer-reviewed journal. The Indian Journal of Pharmaceutics (IJP), is a pharmaceutical journal with international circulation. It publishes original communications of research that advances or illuminates pharmaceutical science or that educates the journal readers. It is issued quarterly, in one volume per year. IJP publishes innovative review article, current opinion, leading article, original research article, short communications and notes dealing with pharmaceutics, pharmaceutical nanotechnology; physical pharmacy; polymer chemistry and physical chemistry as applied to pharmaceutics; excipient function and characterization; biopharmaceutics; absorption mechanisms; membrane function and transport; novel routes and modes of delivery; responsive delivery systems, feedback and control mechanisms including biosensors; applications of cell and molecular biology to drug delivery; prodrug design; bioadhesion; and biotechnology (protein and peptide formulation and delivery).